Ancient indigenous human remains and the law - Batt, Fiona (Routledge research in international law, 2022)
Introduction -- The property narrative: The objectification of ancient indigenous human remains -- The status of ancient indigenous human remains in cultural property and cultural heritage law -- Understanding cultural in the term cultural property and cultural heritage -- Ancient indigenous human remains and ancient indigenous DNA as collective heritage -- Ancient indigenous human remains and ancient indigenous DNA as traditional Knowledge/indigenous knowledge -- Ancient indigenous DNA as intellectual property -- A human rights based approach to the protection and repatriation of ancient indigenous human remains and ancient indigenous DNA -- Using strategic human rights litigation to protect and repatriate ancient indigenous human remains and ancient DNA -- Conclusion